Only time will tell: The interplay between circadian clock and metabolism - Gopalakrishnan, Swetha (Chronobiol Int, 2021)
In most organisms ranging from cyanobacteria to humans, the endogenous timekeeping system temporally coordinates the behavioral, physiological, and metabolic processes with a periodicity close to 24 h. The timing of these daily rhythms is orchestrated by the synchronized oscillations of both the central pacemaker in the brain and the peripheral clocks located across multiple organs and tissues. A growing body of evidence suggests that the central circadian clock and peripheral clocks residing in the metabolically active tissues are incredibly well coordinated to confer coherent metabolic homeostasis. The interplay between nutrient metabolism and circadian rhythms can occur at various levels supported by the molecular clock network, multiple systemic mechanisms, and the neuroendocrine signaling pathways. While studies suggest the reciprocal regulation between circadian clock and metabolism, it is important to understand the precise mechanisms and the underlying pathways involved in the cross-talk among circadian oscillators and diverse metabolic networks. In addition to the internal synchronization of the metabolic rhythms, feeding time is considered as a potential external synchronization cue that fine tunes the timing of the circadian rhythms in metabolic peripheral clocks. A deeper understanding of how the timing of food intake and the diet composition drive the tissue-specific metabolic rhythms across the body is concomitantly important to develop novel therapeutic strategies for the metabolic disorders arising from circadian misalignment. This review summarizes the recent advancements in the circadian clock regulation of nutrient metabolism and discusses the current understanding of the metabolic feedback signals that link energy metabolism with the circadian clock.